Revision of Japanese species of the genus Ecnomus McLachlan (Trichoptera: Ecnomidae), with descriptions of two new species - Kuhara, Naotoshi (Zootaxa, 2016)
Five species of the genus Ecnomus McLachlan (Ecnomidae), including 2 new species, are recognized from Japan: E. hokkaidensis sp. nov. from Hokkaidô and E. sakishimensis sp. nov. from Ishigaki-jima and Iriomote-jima, Ryûkyû Islands, are described. Ecnomus japonicus Fischer, originally described from Kyûshû, is re-described. In addition, illustrations of the male and female genitalia are provided for E. tenellus (Rambur) and E. yamashironis Tsuda, which are common species in Japan. Ecnomus kososiensis Kobayashi, originally described from Honshû, and E. tsudai Kumanski, originally described from Korea, are synonymized under E. tenellus and E. japonicus, respectively.